PUMPA - THE SMART LEARNING APP

AI system creates personalised training plan based on your mistakes

Download now on Google Play
Let us expand some of the squared terms using the suitable standard identities.
1. \((2x+3y)^2\).
 
Let us use the identity, \((a+b)^2\) \(=\) \(a^2+2ab+b^2\).
 
Comparing \((2x+3y)^2\) with \((a+b)^2\), we have \(a=2x\) and \(b=3y\).
 
Substitute the values in the formula.
 
\((2x+3y)^2\) \(=\) \((2x)^2+(3y)^2+2(2x)(3y)\)
 
\((2x+3y)^2\) \(=\) \(4x^2+9y^2+12xy\).
 
 
2. \((5x-7y)^2\).
 
Let us use the identity, \((a-b)^2\) \(=\) \(a^2-2ab+b^2\).
 
Comparing \((5x-7y)^2\) with \((a-b)^2\), we have \(a=5x\) and \(b=7y\).
 
Substitute the values in the formula.
 
\((5-7y)^2\) \(=\) \((5x)^2+ (7y)^2-2(5x)(7y)\)
 
\((5-7y)^2\) \(=\) \(25x^2+49y^2-70xy\).
 
 
3. \((x+5y)(x-5y)\).
 
Let us use the identity, \((a+b)(a-b)\) \(=\) \(a^2-b^2\).
 
Comparing \((x+5y)(x-5y)\) with \((a+b)(a-b)\), we have \(a=x\) and \(b=5y\).
 
Substitute the values in the formula.
 
\((x+5y)(x-5y)\) \(=\)\((x)^2-(5y)^2\)
 
\((x+5y)(x-5y)\) \(=\)\(x^2-25y^2\).
 
 
4. \((4y+5)(4y+3)\).
 
Let us use the identity, \((x+a)(x+b)\) \(=\) \(x^2+(a+b)x+ab\).
 
Comparing \((4y+5)(4y+3)\) with \((x+a)(x+b)\), we have \(x=4y\), \(a=5\) and \(b=3\).
 
Substitute the values in the formula.
 
\((4y+5)(4y+3)\) \(=\) \((4y)^2+(5+3)(4y)+(5)(3)\)
 
\((4y+5)(4y+3)\) \(=\) \(16y^2+32y+15\).
 
Example:
Look for the following cases where we used the identities.
 
1. Expand \((x+4)^2\) using the identity.
 
The above expression is in \((a+b)^2\) form.
 
We have the identity, \((a+b)^2\) \(=\) \(a^2+2ab+b^2\).
 
Substitute \(a = x\) and \(b = 4\) in the formula.
 
\((x+4)^2\) \(=\) \(x^2+2(x)(4)+4^2\)
 
\(=\) \(x^2+2\times 4x+16\)
 
\(=\) \(x^2+8x+16\)
 
 
2. Evaluate \(98^2\) using identity.
 
\(98^2\) \(=\) \((100-2)^2\)
 
The above expression is in \((a-b)^2\) form.
 
We have the identity, \((a-b)^2\) \(=\) \(a^2-2ab+b^2\).
 
Substitute \(a = 100\) and \(b = 2\) in the formula.
 
\((100-2)^2\) \(=\) \(100^2-2(100)(2)+2^2\)
 
\(= 10000-400+4\)
 
\(= 9604\)